2006
DOI: 10.1289/ehp.8149
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Like Properties of Fluorotelomer Alcohols as Revealed by MCF-7 Breast Cancer Cell Proliferation

Abstract: We investigated estrogen-like properties of five perfluorinated compounds using a combination of three in vitro assays. By means of an E-screen assay, we detected the proliferation-promoting capacity of the fluorotelomer alcohols 1H,1H,2H,2H-perfluorooctan-1-ol (6:2 FTOH) and 1H,1H,2H,2H-perfluoro-decan-1-ol (8:2 FTOH). The more widely environmentally distributed compounds perfluoro-1-octane sulfonate, perfluorooctanoic acid, and perfluorononanoic acid did not seem to possess this hormone-dependent proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
70
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 46 publications
7
70
1
Order By: Relevance
“…A significant inhibition of VTG induction was observed upon co-exposure of E2, 4-NP, PFOS, PFOA and 6:2 FTOH with tamoxifen, suggesting that the estrogenic effects of PFCs may be mediated through the ER. Maras et al (2006) demonstrated that 6:2 FTOH, 8:2 FTOH and PFOA caused a significant up-regulation of ER-␣ gene expression, while expression was down-regulated upon exposure to PFOS in MCF-7 breast cancer cells. An in vivo study also demonstrated that ER-␤ was significantly up-regulated in Chinese rare minnow exposed to PFOA (Wei et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A significant inhibition of VTG induction was observed upon co-exposure of E2, 4-NP, PFOS, PFOA and 6:2 FTOH with tamoxifen, suggesting that the estrogenic effects of PFCs may be mediated through the ER. Maras et al (2006) demonstrated that 6:2 FTOH, 8:2 FTOH and PFOA caused a significant up-regulation of ER-␣ gene expression, while expression was down-regulated upon exposure to PFOS in MCF-7 breast cancer cells. An in vivo study also demonstrated that ER-␤ was significantly up-regulated in Chinese rare minnow exposed to PFOA (Wei et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, it seems likely that the binding pool is made up of serum albumins since PFOS is generally bound to serum albumins in common carp (Jones et al, 2003). A previous study by Maras et al (2006) showed that 6:2 FTOH was a stronger xenoestrogen than 8:2 FTOH and they suggested that it is very likely that the chain length of the alkyl group is the responsible factor. As stated above, 8:2 FTOH can be metabolized to PFOA in rats as well as in cultured rat hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have investigated endocrine disruption, such as those of Maras et al (2006) and Vanparys et al (2006) who reported the estrogen-like properties of 6:2 FTOH and 8:2 FTOH in human breast cancer cells (MCF-7). The estrogenic activities were further demonstrated in primary cultured tilapia hepatocytes (Liu et al, 2007) and in Japanese medaka (Ishibashi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, information about toxicological effects of this chemical is just becoming available. [21][22][23] A study on one-generation reproductive toxicity of fluoroalkylethanol mixture having fully fluorinated alkyl chain with six to twelve carbons showed no harmful effect on reproduction in rats. 21) Another study on subchronic toxicity of fluoroalkylethanol mixture demonstrated tooth alterations, hepatocellular hypertrophy, elevation of liver weight and thyroid follicular hypertrophy in rats.…”
mentioning
confidence: 99%
“…22) The subsequent study characterized fluorotelomer alcohols as xenoestrogens in vitro. 23) Thus, information concerning toxicological effects of 8-2 fluorotelomer alcohol is very limited. Therefore, further investigations with regard to biological effects of 8-2 fluorotelomer alcohol are required to provide information for the safe use of this compound.…”
mentioning
confidence: 99%